Synthesis of Melatonin Derivatives and the Neuroprotective Effects on Parkinson’s Disease Models of Caenorhabditis elegans - He, Li; Du, Jing-Jing; Zhou, Jun-Jie; Chen, Meng-Ting; Luo, Lu; Li, Bao-Qiong; Zhang, Xiang-Zhi; Ma, Wen-Zhe; Ma, Ai-Jun; Feng, Na (Frontiers in Chemistry, 2022)
Melatonin (MT) is a hormone with antioxidant activity secreted by the pineal gland in the human brain, which is highly efficient in scavenging free radicals and plays an important role in the neuro-immuno-endocrine system. Emerging evidence showed that melatonin supplementation was a potential therapeutic strategy for Parkinson's disease (PD), which inhibits pathways associated with oxidative stress in PD. In this study, we reported an efficient C7-selective direct olefination of indoles with the aid of the PIII-directed group by rhodium catalysis, and synthesized a series of new indole-C7-cinnamic acid derivatives (6a–6j). Antioxidant potential of the compounds was evaluated both by ABTS and ORAC methods. Among these newly synthesized melatonin derivatives, 6a showed significantly higher activity than MT at 10-5 M. In the transgenic Caenorhabditis elegans (C. elegans) model of PD, 6a significantly reduces α-syn aggregation and dopaminergic neuronal damage in nematodes while reducing intracellular ROS levels, and recovers behavior dysfunction induced by DA neurodegeneration. Further study of the mechanism of action of this compound can provide new therapeutic ideas and treatment strategies for PD.